ASSESSMENT OF KNOWLEDGE AND PRACTICE TOWARD DISPOSAL OF EXPIRED DRUGS AMONG MEDICAL PROFESSIONALS IN CHENNAI - A CROSS-SECTIONAL PROSPECTIVE STUDY - A, Umamageswari; Mv, Guru Scindia; S, Priestly Vivekkumar; R, Geetha (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Proper disposal of expired drugs can avoid drug abuse, drug diversion, environmental contamination, and accidental poisoning by children and animals. Our study was aimed to assess the knowledge and practice toward disposal of expired drugs among medical professionals. Methods: After obtaining verbal consent, a self-administered pretested questionnaire was given to tutors, junior resident, senior resident, assistant professors, associate professors, and professors of Tagore Medical and Dental College and Hospital. The questionnaire has two parts; part one includes demographic details of the study participants, and part two comprises questions, regarding their awareness, knowledge, and practice toward disposal of expired drugs. Data were described as a percentage and analyzed using Sigma Graphpad prism version-5 and Microsoft Excel 2007. Results: A total of 156 medical professionals participated in the study. Among them, 85 were males and 71 were females, whereas 123 (78.8%) were medical and 33 (21.2%) were dental faculties. It was observed that 74.3% of respondents check the expiry date of the drug always and 62.2% said the drug loses its therapeutic effect after the expiry date. Analyzing the method to dispose the expired drugs, 77.6% throw in their household dustbins, 2.6% flush in toilets, 19.2% return to the pharmacist, and 4.5% bury. One-fourth of the medical professionals not aware about environmental hazards due to improper disposal and also believe they do not cause any harm. 64% of preferred pharmacist would be the appropriate person to inform about proper disposal of drugs. Conclusion: This study shows lacunae in the knowledge and practice about proper disposal of expired drugs and recommends discussion regarding improper disposal and its consequences in various health programs.